A donor-acceptor luminogen serving as a haptic film sensor for identity recognition. (February 2022) - Hu, Jiangting; Wu, Miaomiao; Zhao, Xinyi; Duan, Yuai; Yuan, Jing; Han, Tianyu
Abstract: Mechanosensation monitoring is advancing rapidly with the development of haptic sensors. In this study, a donor-acceptor (D-A) luminogen CDBA is reported, which exhibits a transition from intramolecular charge transfer (ICT) state to locally-excited (LE) state in aqueous solution, as well as a stimuli-responsive self-assembly in water vapor. The internal mechanism of the photophysical behavior was probed by spectroscopic analysis and quantum chemical calculation. Based on the remarkable emission turn-on effect in response to water vapor, a haptic film sensor was fabricated. It is highly sensitive to contact pressure, capable of recording the fingerprint with low fingertip pressure. Close inspection using digital single-lens reflex camera and fluorescence microscope demonstrates that the full-scale fingerprint details, including the first-level information (ridges, furrows and skin wrinkles), the second-level information (cores, bifurcations, terminations and islands) and even the third-level information (sweat pores), can be readily collected. In a scenario-based experiment, the pre-placed haptic film sensor succeeded in recording the fingerprint information of a volunteer, suggesting the feasibility for application in security system. Graphical abstract: Image 1 Highlights: A donor-acceptor luminogen with ICT emission sensitive to water. The luminogen is fabricated into a haptic film sensor showing high sensitivity to fingertip pressure. The haptic film sensor can record fingerprint image via finger-pressing. The fingerprint image covering 1–3 level information is available for identity recognition.